Overcoming Challenges to Teamwork in Healthcare: A Team Effectiveness Framework and Evidence-Based Guidance - Zajac, Stephanie; Woods, Amanda; Tannenbaum, Scott; Salas, Eduardo; Holladay, Courtney L. (Frontiers in Communication, 2021)
Background: Safe and effective patient care depends on the teamwork of multidisciplinary healthcare professionals. Unfortunately, the field currently lacks an evidence-based framework for effective teamwork that can be incorporated into medical education and practice across health professions. We introduce a framework for team effectiveness, and an accompanying diagnostic tool. Common challenges to teamwork in healthcare are identified along with evidence-based strategies for overcoming them. Methods: The framework was developed in four steps: (1) grounding in the existing team science literature, (2) semi-structured interviews (N=13), (3) analysis and initial framework development, and (4) revision of the framework through input from healthcare professionals representative of different functions across the healthcare system (N=13). A diagnostic tool consisting of one survey item per team competency was developed to complement the framework. The survey was then administered to healthcare teams across clinical and administrative functions (N=10 teams, 96 individuals), and results were compiled and then used to conduct a debrief with individual team members and teams. A set of common teamwork challenges were identified using the survey and qualitative data. Qualitative data was analyzed to explore the unique ways these challenges manifest in both clinical and administrative teams. Results: The five most common challenges that face healthcare teams relate to accountability, conflict management, decision-making, reflecting on progress, and coaching. These challenges were similar across both clinical and administrative team types. Based on the authors’ collective experience designing and implementing Team Development Interventions (TDIs), strategies for managing each challenge are provided. Conclusions: The proposed framework is unique in two ways. First, it’s generally applicable across the many types of teams that contribute to the quality and safety of patient care. Second, the levels of the framework build upon each other to contribute to the development of the ideal team states. The framework and accompanying strategies can provide guidance for where and how to target developmental efforts.